Forms weakly continuity using weak ω – open sets. Issue 5 (4th July 2021) - Hadi, Mustafa Hasan; AL-Yaseen, May Alaa Abdul-Khaleq; Al-Swidi, Luay A.
Abstract: In this paper, we introduced new types of weak continuity by weakly open sets we have named perfectly ω – continuous, contra – ω – continuous and approximately ω – continuous. As well as we created the relationship between them and also provided some theorems about these types of weak continuous.